1999
DOI: 10.1002/(sici)1097-4547(19990801)57:3<295::aid-jnr1>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Regional distribution of cyclooxygenase-2 in the hippocampal formation in Alzheimer's disease

Abstract: Cyclooxygenase-2 (COX-2), a key enzyme in prostanoid biosynthesis, may represent an important therapeutic target in Alzheimer's disease (AD). In the present study, we explored the regulation of COX-2 in the hippocampal formation in sporadic AD. Using semiquantitative immunocytochemical techniques, we found that in AD cases (vs. age-matched controls) neurons of the CA1-CA4 subdivisions of the hippocampal pyramidal layer showed elevation of COX-2 signal; COX-2 levels correlated with amyloid plaque density. In co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
72
0
3

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 224 publications
(77 citation statements)
references
References 26 publications
2
72
0
3
Order By: Relevance
“…1B) indicated that human COX-2 and the PS1-463 RNA possess relatively short half-lives, of 3 and 4 -5 h, respectively. Conversely, PS2 variants 1 and 2 RNAs have half-lives of Ն10 h, just less than the half-life of ␤-actin RNA, which is Ն12 h (11,33). This is the first report of COX-2 and PS1 RNA half-lives of ϳ3-5 h in primary human neural cells; these are analogous to COX-2 half-lives found in human IMR-90 and temporal lobe neocortex (9).…”
Section: Cox-2/ps1 Gene Activation In Ad Brainmentioning
confidence: 52%
See 2 more Smart Citations
“…1B) indicated that human COX-2 and the PS1-463 RNA possess relatively short half-lives, of 3 and 4 -5 h, respectively. Conversely, PS2 variants 1 and 2 RNAs have half-lives of Ն10 h, just less than the half-life of ␤-actin RNA, which is Ն12 h (11,33). This is the first report of COX-2 and PS1 RNA half-lives of ϳ3-5 h in primary human neural cells; these are analogous to COX-2 half-lives found in human IMR-90 and temporal lobe neocortex (9).…”
Section: Cox-2/ps1 Gene Activation In Ad Brainmentioning
confidence: 52%
“…COX-2 expression may be further induced in astrocytes and microglia in response to elevated A␤42 and/or IL-1␤ during aging or in AD (5-9), because both cytokines and ROS trigger NF-Bp50/p65-mediated transcription from COX-2 and related inflammatory genes (9 -14). Moreover, although the majority of gene transcripts are down-regulated in AD hippocampus (4,9,13,21,43,44), certain RNAs encoding inflammatory mediators exhibit overexpression (7)(8)(9)(10)(11)(12)(13). COX-2 and PS1 RNA message in human embryonic (E7-E30) and adult (1-75 years) brain coincides with the most active neurogenesis, followed by coordinate downregulation of COX-2 and PS1 RNA abundance during aging (r 2 ϭ 0.9, p Ͻ 0.03; Fig.…”
Section: Cox-2 and Ps1mentioning
confidence: 95%
See 1 more Smart Citation
“…Inflammatory stimuli such as lipopolysaccharide (LPS) and cytokines such as TNF␣ and IL-1␤ have been found to enhance COX-2 expressions in microglia (Minghetti and Levi, 1995;Bauer et al, 1997). In pathological conditions, elevated COX-2 expressions have been observed in AD brain and ALS spinal cord (Ho et al, 1999;Yasojima et al, 1999Yasojima et al, , 2001.…”
Section: Introductionmentioning
confidence: 99%
“…Um possível modo de ação para a eficácia dos antiinflamatórios não-esteroidais seria o bloqueio específico da isoforma ciclooxigenase-2 (COX-2) no cérebro de pacientes portadores da doença de Alzheimer 42 . Estudos têm demonstrado que o RNA mensageiro (RNAm) da COX-2 esteve consideravelmente aumentado em áreas afetadas pela doença de Alzheimer 48 , sugerindo o envolvimento da COX-2 nessa doença. De fato, a aplicação de Aβ (1-42) (5 microM) em culturas humanas de micróglia durante 8 horas induziu a expressão e o aumento da produção das citocinas pró-inflamatórias IL-6, IL-1β, TNF-α, da COX-2 e IL-8 48 .…”
Section: A Doença De Alzheimer E Os Antiinflamatóriosunclassified